Исследование влияния типа инертного газа на процесс плазмодинамического синтеза оксидов железа - Циммерман А. И. Александр Игоревич; Шаненков И. И. Иван Игоревич; Сивков А. А. Александр Анатольевич; Ивашутенко А. С. Александр Сергеевич; Насырбаев А. Артур; Власов В. А. Виталий Анатольевич (2022, 2022)
Заглавие с экрана